Weight self‐stigma and weight loss during behavioural weight loss intervention - J. Lillis; J. G. Thomas; K. Olson; R. R. Wing (Wiley, 2019)
Summary Objective Despite the myriad negative effects of weight self‐stigma, its role in weight loss intervention has not been thoroughly examined. The aim of this study was to examine the association between weight self‐stigma and weight loss. Methods This longitudinal study examined the association between weight loss and changes in self‐stigma, assessed by the Weight Self‐Stigma Questionnaire, which distinguished between self‐devaluation and fear of enacted stigma. Participants were adults with overweight or obesity enrolled in a 24‐month weight loss intervention trial (groups were collapsed for this post hoc analysis) who were assessed at baseline, 6, 12, 18 and 24 months. Results Baseline levels of self‐stigma were not associated with weight loss outcomes. However, mixed models analysis showed that reductions in one aspect of weight self‐stigma, self‐devaluation, was associated with greater weight loss (p = 0.01). Cross products mediation analysis showed that increases in use of weight control strategies mediated the association between reductions in self‐devaluation and greater weight loss (F = 14.86, p < 0.001; CI 0.09-0.37). Conclusions Results suggest that there may be potential for incorporating intervention methods targeting the reduction of self‐stigma in order to improve weight loss outcomes.